Sensorimotor coordination and determination ability of computer gamer and non-gamer sportspersons - Acharya, J.; Pandey, V.; Mishra, A. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
This study examined and compared the sensorimotor coordination hypothesis and determination ability hypothesis as explanations for computer gamer and non-gamer sportspersons. The study was conducted on 20 randomly selected male sportspersons (10 each in gamer [minimum 8 hours per-week] and non-gamer [who never play any kind of computer game]) in the age group 18-25 years with a mean & SD of 20.95 ± 2.19. For measuring sensorimotor coordination and determination, Vienna test system (VTS), a computerized psychological assessment tool was used. Independent `t` test was applied at 0.05 level of significance and its various assumptions of normality (Shapiro-Wilk test), outliers (box plots) and homogeneity of variances (Levene`s test for homogeneity of variances) were tested. The results revealed that there is statistically significant difference in the mean of sensorimotor coordination score (8.90, p = .00) and determination test incorrect score (3.64, p = .00) between gamers and non-gamers at 18df. These results suggest that the sportspersons who play computer games have better sensorimotor coordination and determination ability when tested in VTS. Future research should combine sport performance and these methods to gain a more complete understanding of this phenomenon.